Assimilation effects on infant mortality among immigrants in Norway - Jonas Minet Kinge; Tom Kornstad (Statistics Norway, Research Department, 2013)
The wellbeing of children of immigrant mothers is of great concern worldwide. In this study, we investigate the relationship between infant mortality and maternal country of origin and whether or not this relationship varies with the number of years since maternal migration. We use an extensive dataset consisting of all births in Norway from 1992 to 2010 augmented by source country and other maternal characteristics. By measuring the source country infant mortality rate at the time the mother came to Norway, we are able to account for circumstances in the country the mother left behind. There are two main findings. Firstly, maternal source country characteristics are significantly associated with the infant mortality rate in Norway. Those with a maternal background from countries with a high infant mortality rate (e.g. countries in Africa and Asia) have a persistently higher infant mortality rate than those from countries with a low infant mortality rate (e.g. countries in Europe). Secondly, an assimilation process takes place, since the effect of maternal source country characteristics declines with the number of years since maternal migration. Hence, those with a nonnative maternal background have a higher infant mortality rate upon arrival, but the gap is eliminated after 20 years in Norway. The results cannot be explained by observable characteristics such as maternal age at birth, area of residence, maternal education or marital status.
Keywords: J15; J13; J18; I10; 330; Infant mortality; Immigration; Assimilation